ANALISIS TINGKAT KESULITAN SISWA DALAM MENYELESAIKAN SOAL IPA SISWA KELAS V SDN 61 MARIO KECAMATAN PONRANG KABUPATEN LUWU - Nurasia; Erni; Rasna Sarira (Jurnal Biogenerasi, 2022)
This study aims to analyze the level of difficulty of students in solving science problems. This type of research is descriptive quantitative research. The subjects in this study were the fifth grade students of SDN 61 Mario, Ponrang District, Luwu Regency with a total of 19 students. Data collection techniques in this study consisted of tests. The research instrument used was an essay test which consisted of 5 essay questions. The results of this study indicate that the results of students' science difficulty tests based on existing data, students' difficulties in solving science questions for cognitive level C1 generally answered correctly with a percentage of 63.16%, while for cognitive level 2 generally answered almost correctly with a percentage of 78, 95% and for the cognitive level C3 generally answered incorrectly with a percentage of 57.89%. Thus, it can be concluded that the fifth grade students of SDN 61 Mario generally have difficulty answering questions at the C3 cognitive level.